Around 1987: outline of a lesson in geographic thought. Issue 2 (June 2014) - Cresswell, Tim
<x xml:space="preserve">Abstract</x> This short commentary reflects on Philo's 1987 Area paper, ' "Not at our seaside": community opposition to a nineteenth‐century branch asylum' by placing it in the context of currents of thought emerging or coalescing in that year as well as my own intellectual trajectory. These contexts include the emerging interest in Foucault, developments in cultural, social and historical geography and the long‐standing interest in the significance of 'outsiders' and their role in the production of order. Most of all, perhaps, the paper prefigures Philo's own career with its consistent interest in (and sympathy for) outsiders, engagement with wider currents of theory (particularly Foucault) and insistence on the importance of history.